14-3-3 proteins: eukaryotic regulatory proteins with many functions - Finnie, C; Borch, J; Collinge, D.B (Plant molecular biology, 1999)
The enigmatically named 14-3-3 proteins have been the subject of considerable attention in recent years since they have been implicated in the regulation of diverse physiological processes, in eukaryotes ranging from slime moulds to higher plants. In plants they have roles in the regulation of the plasma membrane H(+)-ATPase and nitrate reductase, among others. Regulation of target proteins is achieved through binding of 14-3-3 to short, often phosphorylated motifs in the target, resulting either in its activation (e.g. H(+)-ATPase), inactivation (e.g. nitrate reductase) or translocation (although this function of 14-3-3 proteins has yet to be demonstrated in plants). The native 14-3-3 proteins are homo- or heterodimers and, as each monomer has a binding site, a dimer can potentially bind two targets, promoting their association. Alternatively, target proteins may have more than one 14-3-3-binding site. In this mini review, we present a synthesis of recent results from plant 14-3-3 research and, with reference to known 14-3-3-binding motifs, suggest further subjects for research.